2014
DOI: 10.1080/15287394.2014.886543
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Persistent Organic Pollutants and Circulating Immunoglobulin-Y in Black-Legged Kittiwakes and Atlantic Puffins

Abstract: Have Although persistent organic pollutants (POPs) may affect the immune system, few field studies actually examined this effect. There are indications that POP exert effects on the immune system; however, in the Arctic ecosystem data are scarce. The aim of this study was to examine immune functions in two medium trophic-positioned seabirds, the black-legged kittiwakes (Rissa tridactyla) and Atlantic puffins (Fratercula arctica). Overall POP concentrations were higher in kittiwakes than puffins and males had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…A study performed in Artic glaucous gulls (Larus hyperboreus) showed a negative correlation between chick body condition and the parent´s blood levels of HCB and PCBs (Gabrielsen 2007). Another work showed a negative response between POPs and IgY in Atlantic puffins (Fratercula arctica) (Sagerup et al 2014). Similarly, our results showed that the chinstrap penguin colonies at Cape Shirreff exhibited the highest concentrations of PCBs with the lowest IgY response, although with low exposure levels.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…A study performed in Artic glaucous gulls (Larus hyperboreus) showed a negative correlation between chick body condition and the parent´s blood levels of HCB and PCBs (Gabrielsen 2007). Another work showed a negative response between POPs and IgY in Atlantic puffins (Fratercula arctica) (Sagerup et al 2014). Similarly, our results showed that the chinstrap penguin colonies at Cape Shirreff exhibited the highest concentrations of PCBs with the lowest IgY response, although with low exposure levels.…”
Section: Discussionsupporting
confidence: 69%
“…Also, our HCB, PCB-118, PCB-138, PCB-153 and PCB-180 concentrations are lower than those levels reported by Sagerup et al (2014) in blood of blacklegged kittiwakes (Rissa tridactyla) from the Artic (3.80,4.87,18.39,12.43 and 2.27 ng/g, respectively), and they are not likely to be a threat for this population. However, even if concentrations of these pollutants are low, they may have a combined effect with some others chemicals, such as heavy metals (Sebastiano et al 2016).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations